2018
DOI: 10.1021/acs.jpcc.8b08335
|View full text |Cite
|
Sign up to set email alerts
|

Electrolyte-Assisted Hydrogen Storage Reactions

Abstract: Use of electrolytes, in the form of LiBH 4 /KBH 4 and LiI/KI/CsI eutectics, is shown to significantly improve (by more than a factor of ten) both the dehydrogenation and full rehydrogenation of the MgH 2 /Sn destabilized hydride system and the hydrogenation of MgB 2 to Mg(BH 4 ) 2 . The improvement revealed that inter-particle transport of atoms heavier than hydrogen can be an important rate-limiting step during hydrogen cycling in hydrogen storage materials consisting of multiple phases in powder form. Electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…Magnesium diboride (MgB 2 ) is a fascinating material, not only for its superconducting properties but also for its ability to store hydrogen in the form of magnesium borohydride [Mg­(BH 4 ) 2 ]. While Mg­(BH 4 ) 2 has an exceptionally high hydrogen gravimetric capacity of 14.9%, once it releases hydrogen to form MgB 2 , it is challenging to rehydrogenate MgB 2 back to Mg­(BH 4 ) 2 . As first observed by Severa et al and reviewed by Ray and co-workers, the complete conversion of MgB 2 to Mg­(BH 4 ) 2 requires excessively high pressures (950 bar) and temperatures (400 °C).…”
Section: Introductionmentioning
confidence: 99%
“…Magnesium diboride (MgB 2 ) is a fascinating material, not only for its superconducting properties but also for its ability to store hydrogen in the form of magnesium borohydride [Mg­(BH 4 ) 2 ]. While Mg­(BH 4 ) 2 has an exceptionally high hydrogen gravimetric capacity of 14.9%, once it releases hydrogen to form MgB 2 , it is challenging to rehydrogenate MgB 2 back to Mg­(BH 4 ) 2 . As first observed by Severa et al and reviewed by Ray and co-workers, the complete conversion of MgB 2 to Mg­(BH 4 ) 2 requires excessively high pressures (950 bar) and temperatures (400 °C).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, chemical doping by secondary species with predominantly ionic interactions (e.g., alkali and alkaline earth metals) could facilitate changes in B and H bonding configurations at MgB 2 edges, particularly if these dopants segregate naturally to reactive edges, interfaces, and grain boundaries where the highest reactivity is likely to be found. This may relate to the recently reported kinetic enhancement of MgB 2 hydrogenation by addition of an electrolyte solution comprised of LiI/KI/CsI or LiBH 4 /KBH 4 …”
Section: Discussionmentioning
confidence: 72%
“…This may relate to the recently reported kinetic enhancement of MgB 2 hydrogenation by addition of an electrolyte solution comprised of LiI/KI/CsI or LiBH 4 /KBH 4 . 39 We can further speculate regarding the evolution of the MgB 2 edge-plane chemistry as the reaction proceeds. Although the B-terminated edge planes are generally more reactive, we find a thermodynamic driving force toward Mg-terminated edge planes.…”
Section: Discussionmentioning
confidence: 92%
“…Then the desired amount (0.50 g) of this mixture was lightly mixed using a spatula with the lithium aluminum hydride mixture (0.51 g). Previous differential scanning calorimetry (DSC) measurements confirmed that eutectic melting occurred from the ground mixture during the initial heating at ~110 • C. [15].…”
Section: Methodsmentioning
confidence: 93%
“…It was recently demonstrated that the presence of a liquid electrolyte (under reaction conditions), in the form of a eutectic, significantly increases the dehydrogenation and rehydrogenation reaction rates in some hydrides [15]. It has been suggested that the electrolyte substantially increases the reaction interface area as well as transport of heavy ions.…”
Section: Introductionmentioning
confidence: 99%